Nonribosomal cyclic peptides: specific markers of fungal infections - Jegorov, Alexandr; Hajduch, Marian; Sulc, Miroslav; Havlicek, Vladimir (Journal of mass spectrometry, 2006)
Some cyclic peptides and depsipeptides are synthesized in microorganisms by large multienzymes called nonribosomal peptide synthetases. The structures of peptide products originating in this way are complex and diverse and are microorganism-specific. This work proposes the use of fungal cyclic peptides and depsipeptides as extremely specific markers of fungal infections. Since a reliable molecular tool for diagnosing fungal infections at an early stage is still missing, we present mass spectrometry as a new, modern, broadband (with respect to fungal strain) and specific tool for clinical mycologists. More than 40 different fungal species can be rapidly characterized according to specific families of cyclic peptides, and in some cases, a particular fungal strain can be identified on the basis of its cyclopeptide profile. This paper is also aimed at initiating discussion on the biological role of these secondary metabolites, especially of those synthesized by medically important strains. Proven cytotoxic, anti-inflammatory or immunosuppressive activities of some cyclic peptides indicate that these molecules may contribute to the synergistic array of fungal virulence factors and support microbial invasion during fungal infection. In addition to an overview on recent mass spectrometric protocols for cyclic peptide sequencing, the structures of new peptides from Paecilomyces and Pseudallescheria are presented.
Keywords: mykózy; Peptide Biosynthesis, Nucleic Acid-Independent; fungální proteiny; biosyntéza peptidů nezávislá na nukleových kyselinách; biologické markery; Humans; Mass Spectrometry; Mycoses; lidé; Biomarkers; hmotnostní spektrometrie; Microbiological Techniques; mikrobiologické techniky; Fungal Proteins